Scleredema of Buschke in a little child and its successful treatment with ultraviolet A1 phototherapy - Damla Demir; Müge Göre Karaali; Filiz Cebeci Kahraman; İlkin Zindancı; Ebru Zemheri (Galenos Publishing House, 2022)
A 5-year-old girl with skin hardness and thickening was admitted to our clinic and diagnosed with scleredema of Buschke clinically and histopathologically. Ultraviolet A1 (UVA1) phototherapy at a dose of 30 J/cm2 was planned for 3 days in 1 week. After 45 UVA1 phototherapy sessions (with a cumulative dose of 1350 J/cm2), clinical complete remission was achieved. Ultrasonography revealed improvement in skin thickening, and no recurrence was noted in the 2-year follow-up period.